METHODOLOGY FOR FORMING SPATIAL REPRESENTATIONS IN PRIMARY SCHOOL MATHEMATICS TEXTBOOKS (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
This article explores effective methodologies for forming spatial representations in primary school students through mathematics textbooks. The development of spatial thinking is considered a fundamental component of mathematical competence, especially in early education. The study analyzes the content, structure, and didactic potential of primary school mathematics textbooks, focusing on how geometric materials contribute to the formation of spatial imagination.